2018
DOI: 10.1093/cercor/bhy323
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Related Changes in Cognition and Cortical Integrity are Associated With Serum Expression of Candidate MicroRNAs for Alzheimer Disease

Abstract: Evidence has shown that microRNAs (miRNAs) are involved in molecular pathways responsible for aging and prevalent aging-related chronic diseases. However, the lack of research linking circulating levels of miRNAs to changes in the aging brain hampers clinical translation. Here, we have investigated if serum expression of brain-enriched miRNAs that have been proposed as potential biomarkers in Alzheimer’s disease (AD) (miR-9, miR-29b, miR-34a, miR-125b, and miR-146a) are also associated with cognitive functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…To date, a number of miRNAs have been reported to have crucial roles in neurogenesis and neuronal maturation in the CNS (33). Significant differences have been detected regarding miRNA expression levels between AD patients and healthy individuals (34). miRNAs represent a novel class of biomarkers for AD, which are non-invasive and sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of miRNAs have been reported to have crucial roles in neurogenesis and neuronal maturation in the CNS (33). Significant differences have been detected regarding miRNA expression levels between AD patients and healthy individuals (34). miRNAs represent a novel class of biomarkers for AD, which are non-invasive and sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAES3 was also found to act as a competing endogenous RNA (ceRNA) of miR-34c-5p to enhance BMF expression [61]. 12 Table 1). According to a study by Du et al [62], miR-17 extends the lifespan of transgenic mice by upregulating MKP and FoxO3 and downregulating mTOR and JNK through two targets, ADCY5 and IRS1.…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…According to the UNESA population division, approximately 900 million people are 60 years or older worldwide, and this will increase to 21.5% of the global population by 2050 [3] (see Figure 1). As aging progresses, it increases one's susceptibility to diseases associated with this process, such as vascular aging disorders [4][5][6], diabetes [7], muscle dysfunction [8,9], macular degeneration [10], Alzheimer's disease (AD) [11,12], skin diseases [13], and a series of other diseases [14][15][16][17][18] (see Figure 2). Aging-related diseases pose a serious threat to human health and reduce the quality of life among elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…Independent of these exosome RNA studies, others have shown that specific miRNAs are involved in ageassociated changes in the brain as well as cognitive impairment. Candidate miRNAs have been linked to age-associated alterations in cortical thickness, cortical glucose metabolism, and cognitive performance (Maldonado-Lasuncion, Atienza, Sanchez-Espinosa, & Cantero, 2018). These include for example miR29-b, miR-125b, and miR-146a-miRNAs which have all been found in exosomal cargo (Kim et al, 2015;Mathivanan et al, 2012).…”
Section: Exosome Rna Cargomentioning
confidence: 99%